(untitled) (AYUSHDHARA, 2022)
Pain is an unpleasant sensory and emotional experience associated with actual or potential tissue damage. It is said to be nature’s earliest sign of morbidity and it is prominent among all the other sensory experiences by which an individual can identify the presence of a pathological condition in them. In the condition related to musculo-skeletal system, pain is an important symptom. The most common cause of joint pain is either inflammation or degeneration. Some of the conditions with joint pain due to inflammation are Rheumatoid Arthritis (RA), psoriatic arthritis, ankylosing spondylitis, Systemic Lupus Erythematous (SLE), Gouty arthritis. References regarding different conditions related to Joint is seen in the context of many systemic diseases like Jwara, Atisara, Grahani, Pandu, to mention a few, and Sandhi (joints) related diseases like Amavata, Vatarakta, Vatavyadhi and Kroshtukaseersha, in Ayurveda. The Samprapti (pathogenesis) can be thought to be due to the involvement of Tridoshas, Ama and Rakta. Due to the Khavaigunya and Vakrata of the Sandhis, they get lodged at the Sandhi Pradesha resulting in symptoms of Inflammatory Arthritis such as Vedana (pain), Sopha (swelling), Raga (redness) and Sparshasahishnuta (tenderness) in Sandhi.